Quality of Hypospadias Surgery in a High Volume Hospital: Review of Short to Medium-Term Outcomes after Snodgrass Hypospadias Repair - Haroon, Naveed; Asif, Muhammad; Ullah , Maryam Ikram; Khan, Zakir; Rehman, Shahzad Ur; Anwar, Kausar; Bibi, Romana (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES The study aimed to review short-term and medium-term outcomes of Snodgrass repair from one-year to two-year follow-up. METHODOLOGY It’s a retrospective review of 114 patients (secondary data) with distal penile hypospadias without curvature who underwent Snodgrass repair performed by a single surgeon in the department of Urology, Lady Reading Hospital Peshawar from March 2021 to March 2022. Hypospadias objective score Evaluation (HOSE) was used for functional and cosmetic outcomes. RESULTS The mean age at the time of presentation for surgery was 3 years. The mean documented follow-up was 13 months (2-23 months). 51% (58) of patients presented with coronal hypospadias, followed by sub-coronal, distal and glanular hypospadias. Overall complication rate was 10%. Three patients developed a total breakdown of their wounds that needed further staged procedures. Meatal stenosis was noted in three patients requiring meatal dilatation, and another two came back with non-obliterative strictures. One had gentle dilatation, and the other underwent an optical urethrotomy. The rest of the four patients developed urethrocutanoeus fistulae (UCF), ultimately getting repaired 6 months postoperatively. Good cosmetic and functional results were achieved in 93% of cases (HOSE score of 14 or above). CONCLUSION This study shows that Snodgrass repair is the best option for mainly correcting distal penile and midshaft hypospadias and has an acceptably low complication rate with better short to medium-term outcomes.